PENGARUH STRATEGIC ORIENTATION, GOVERNMENT REGULATION DAN GREEN ECONOMY TERHADAP GREEN SUPPLY CHAIN MANAGEMENT PADA PT. HEINZ ABC INDONESIA - Harsono, Diwa Yudo; Alhazami, Lutfi (Lembaga Pengembangan Kinerja Dosen, 2023)
Global warming is a global phenomenon triggered by human activities related to the use of fossil fuels and deforestation which is increasingly widespread throughout the world. This study uses a survey method with a quantitative approach. This research was conducted at PT Heinz Jakarta. The sampling technique used is probability sampling with simple random sampling technique, the population is taken randomly without regard to the existing strata in the population. As well as statements that measure research variables, namely the Effect of Strategic Orientation, Government Regulation, Green Economy. The process of collecting questionnaire data is carried out online.